Development of Student Worksheet based on Problem-Based Learning (PBL) on Critical Thinking Ability - Nurwulandari, Nira; Marfu'ah, Siti (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
The research aims to: (1) Determine the effectiveness of the science process skills approach in achieving 75% of students passing the Minimum Competency Criteria (KKM), (2) Determine the effectiveness of the science process skills approach in improving conceptual understanding of static fluids, (3) Determine the effectiveness of the science process skills approach in increasing learning motivation. This research is a quasi-experimental study with a pretest-posttest control group design. The independent variable in this research is the science process skills approach, and the dependent variables are conceptual understanding and learning motivation in physics. The sampling technique used is simple random sampling. Data analysis techniques include t-tests, normalized gain, and effect size. The results of this study show: (1) The science process skills approach is not effective in achieving 75% of students passing the KKM, as only 62.5% of students passed the KKM, (2) The science process skills approach is effective in improving conceptual understanding of static fluids (sig 2-tailed = 0.000 < α = 0.05, thus Ha is accepted and Ho is rejected) and improves conceptual understanding with an N-gain of 0.68 (moderate) and an effect size of 1.46, (3) The science process skills approach is effective in increasing motivation in learning physics, with an N-gain of 0.39 (moderate).